Analysis of the Role of Payroll Accounting Information Systems in Supporting the Effectiveness of Internal Controls at Regional Water Company TIRTANADI North Sumatra - Dewi Sartika Nasution; Saparuddin Siregar (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Payroll accounting system is a system that was formed to secure the problem of paying salaries in a company. A good system will create effective company internal controls so as to reduce fraud in the company. The purpose of this literature is to analyze the role of payroll accounting information systems in supporting the effectiveness of internal control at PDAM Tirtanadi, North Sumatra. This literature is a field research using a qualitative descriptive method. The type of data used by the author in this research is qualitative data, in the form of non-numeric data obtained from interviews and observations. The author uses the origin of the data in this article which was obtained by referring to primary data sources in the form of literature studies. The data analysis technique used by the author in this research is to use descriptive analysis techniques. The procedures applied in the payroll system already look quite good, each procedure is always corrected for correctness and suitability before proceeding to the next payroll step. The documents used are also complete to support the effectiveness of the payroll system at PDAM Tirtanadi, this can be seen from the computerized payroll system